Sosial Religius dalam Perspektif Islam dan Kristen - Nafis, Mhd. Ad-Darrun; Kamaluddin, Kamaluddin; Ekowati, Endang (YASIN, 2023)
This study aims to find out how social religious urgency is in the views of Islam and Christianity and find out how social religious similarities and differences in the views of Islam and Christianity. In this study, researchers used a type of library research (library research). This research uses the Sociology of Religion approach method. The sociology of religion approach is an approach that discusses one of the social phenomena, namely religion as a social manifestation. The results of this study are that social religion is an act based on awareness or a tendency to pay attention to the public interest in accordance with religious rules. In Islam, social religious pressure is very important to build a good relationship between individuals with God and fellow human beings. Meanwhile, in the Christian view, social religion also emphasizes the importance of the individual's relationship with God and fellow human beings. Christianity prohibits that love is the main principle in living a social-religious life. Mukti Ali's views on social religion in Islam emphasize the values of solidarity, social justice, social responsibility, and interfaith dialogue. He described the importance of the active role of Muslims in society to create a better and harmonious life based on Islamic teachings.